2019
DOI: 10.3390/rs11060682
|View full text |Cite
|
Sign up to set email alerts
|

Wide Field of View Microwave Interferometric Radiometer Imaging

Abstract: In microwave interferometric radiometers with a large field of view, as for example the Microwave Imaging Radiometer with Aperture Synthesis (MIRAS) onboard the Soil Moisture and Ocean Salinity (SMOS) satellite, one of the major causes of reconstruction error is the contribution to the visibility of the brightness temperature outside the fundamental period, defined on the basis of reciprocal grids. A mitigation method consisting of estimating this contribution through the application of a brightness temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The up-to-date methods developed by the UPC in the recent years for reducing image reconstruction errors are also included in the MTS. Details on the used image reconstruction strategy can be found in Corbella et al (2009Corbella et al ( , 2019. Corbella et al (2015) showed that the dominant contribution to both Land/Sea Contamination (LSC) and the Ice/Sea Contamination (ISC) comes from residual multiplicative errors and proposed a 2% correction factor to the MIRAS correlator efficiencies (also known as the G kj correction).…”
Section: Generation Of Brightness Temperaturesmentioning
confidence: 99%
“…The up-to-date methods developed by the UPC in the recent years for reducing image reconstruction errors are also included in the MTS. Details on the used image reconstruction strategy can be found in Corbella et al (2009Corbella et al ( , 2019. Corbella et al (2015) showed that the dominant contribution to both Land/Sea Contamination (LSC) and the Ice/Sea Contamination (ISC) comes from residual multiplicative errors and proposed a 2% correction factor to the MIRAS correlator efficiencies (also known as the G kj correction).…”
Section: Generation Of Brightness Temperaturesmentioning
confidence: 99%
“…We use the MIRAS Testing Software (MTS) to obtain SMOS brightness temperatures at antenna reference frame from ESA SMOS Level 0 data (Corbella et al, 2008(Corbella et al, , 2009(Corbella et al, , 2019. We use ALL-LICEF mode as a calibration approach (Corbella et al, 2016) because with this calibration mode the measurements of the antenna temperature (zero-baseline visibility) and the rest of the visibility samples are more consistent.…”
Section: Brightness Temperatures Generationmentioning
confidence: 99%
“…In an interferometric radiometer such as MIRAS, M kj is measured by a complex correlator, the system temperatures T sys k,j by "Power Measurement Systems" (PMS) included in each receiver, and G kj by internal calibration injecting correlated noise [9,10]. The visibility V kj is then solved from the above equation, and the brightness temperature is finally obtained by inverting the visibility equation [11].…”
Section: Visibility and Correlationmentioning
confidence: 99%
“…in which (11) was used. This operation can be carried out for each individual receiver to obtain its corresponding center frequency, which in general are different from each other.…”
Section: Center Frequency Errormentioning
confidence: 99%